THE ROLE OF WAKAF IN EMPOWERING LOCAL ECONOMIES: A STUDY OF ITS POTENTIAL IN MODERN ISLAMIC FINANCE - Muntadhirotul Maghfiroh, Ana (CV. Lafadz Jaya, 2024)
Wakaf, as an integral component of Islamic philanthropy, has long played a crucial role in the socio-economic development of Muslim communities. Traditionally used for religious and charitable purposes, the concept of wakaf has evolved to serve a broader spectrum of needs in modern Islamic finance. This paper explores the potential of wakaf in empowering local economies by channeling its resources towards sustainable economic development. Through case studies and analysis of successful wakaf-based projects, the paper demonstrates how wakaf institutions can provide financial resources for infrastructure development, education, healthcare, and small-to-medium enterprises (SMEs). Moreover, the research highlights the role of innovative Islamic financial instruments, such as cash wakaf and sukuk wakaf, in unlocking the untapped potential of wakaf assets. The findings suggest that, with proper management, wakaf can significantly contribute to poverty alleviation, job creation, and overall economic empowerment. However, the paper also addresses the challenges facing wakaf institutions, including regulatory constraints, governance issues, and a lack of public awareness. The study concludes with policy recommendations for maximizing the socio-economic impact of wakaf within the framework of modern Islamic finance, emphasizing the need for stronger institutional support and more strategic collaboration between stakeholders.